A rare variant of the leptin gene has large effects on blood pressure and carotid intima-medial thickness: a study of 1428 individuals in 248 families. Issue 6 (3rd June 2005) - Gaukrodger, N; Mayosi, B M; Imrie, H; Avery, P; Baker, M; Connell, J M C; Watkins, H; Farrall, M; Keavney, B
Abstract : Background: Rare mutations in the leptin ( LEP ) gene cause severe obesity. Common polymorphisms of LEP have been associated with obesity, but their association with cardiovascular disease has been little studied. We have examined the impact of both common and rare polymorphisms of the LEP gene on blood pressure (BP), subclinical atherosclerosis as measured by carotid intima-medial thickness (CIMT), and body mass index (BMI) in a large family study. Methods: Five polymorphisms spanning LEP were typed in 1428 individuals from 248 nuclear families. BP, CIMT, BMI, and plasma leptin were measured. Results: The polymorphisms typed captured all common haplotypes present at LEP . There was strong association between a rare polymorphism in the 3′ untranslated region of LEP (C538T) and both pulse pressure (p = 0.0001) and CIMT (p = 0.008). C/T heterozygotes had a 22% lower pulse pressure and a 17% lower CIMT than C/C homozygotes. The polymorphism accounted for 3–5% of the population variation in pulse pressure and CIMT. There was no association between any LEP polymorphism and either BMI or plasma leptin level. Conclusions: This large family study shows that the rare T allele at the C538T polymorphism of LEP substantially influences pulse pressure and CIMT, but does not appear to exert this effect through actions on plasma leptin level or BMI. This suggests that autocrine or paracrine effects in vascular tissue may be important physiological functions of leptin. This study also provides evidence that rare polymorphisms of particular genes may have substantial effects within the normal range of certain quantitative traits.